Sesquiterpene lactones isolated from indigenous Middle Eastern plants inhibit tumor promoter-induced transformation of JB6 cells - Saikali Melody; Ghantous Akram; Halawi Racha; Talhouk Salma N; Saliba Najat A; Darwiche Nadine (BMC, 2012)
Abstract Background Sesquiterpene lactones (SL) are plant secondary metabolites that are known for their anti-fungal, anti-bacterial, anti-inflammatory, and anti-tumor properties. Considering that several SL-derived drugs are currently in cancer clinical trials, we have tested two SL molecules, 3-β-methoxy-iso-seco-tanapartholide (β-tan) isolated from Achillea falcata and salograviolide A (Sal A) isolated from Centaurea ainetensis, for their anti-tumor properties. We used the mouse epidermal JB6P + cells as a model for tumor promotion and cellular transformation. Key players that are involved in cellular transformation and tumorigenesis are the AP-1 and NF-κB transcription factors; therefore, we assessed how β-tan and Sal A modulate their signaling pathways in JB6P + cells. Methods The effects of β-tan and Sal A on the growth of normal and neoplastic keratinocytes and on the tumor promotion-responsive JB6P + cells were determined using the MTT assay. Anchorage-independent cell growth transformation assays were used to evaluate the anti-tumor promoting properties of these SL molecules in JB6P + cells and dual luciferase reporter assays and western blot analysis were used to investigate their effects on tumor promoter-induced AP-1 and NF-κB activities and protein levels of key AP-1 and NF-кB target genes. Results β-tan and Sal A selectively inhibited tumor promoter-induced cell growth and transformation of JB6P + cells at concentrations that do not affect JB6P + and primary keratinocytes basal cell growth. In addition, both molecules reduced basal and tumor promoter-induced NF-κB transcriptional activities, differentially regulated basal and tumor promoter-induced AP-1 transcriptional activities, and modulated key players of the AP-1 and NF-κB signaling pathways. Conclusions These results highlight the anti-tumor promoting properties of β-tan and Sal A. These SL molecules isolated from two plant species native to the Middle East may provide opportunities for complementary medicine practices.